The effects of interaction between smoking and abdominal obesity on pre-diabetes mellitus - Huali Xiong; Peng Zhao; Fengxun Ma; Dayi Tang; Daiqiang Liu (Scientific Reports)
Abstract Limited studies have been conducted on the interaction of smoking and abdominal obesity on the risk of pre-diabetes mellitus (PDM) among rural adults in southwest China. The data was obtained from a cross-sectional survey conducted using a two stage random sampling method around Rongchang district in ChongQing municipality southwest of China in 2022. A total of 3,017 participants aged 40 to 79 years old were included in the study. Multivariate logistic regression analyses were performed to evaluate the associated risk factors for PDM, and the effect of multiplicative and additive interactions between smoking and abdominal obesity were also assessed by indicators including the relative excess risk due to interaction (RERI), the attributable proportion due to interaction (AP) and the synergy index (SI). We found that the prevalence of PDM in participants was 38.98% with an average age of (62.14 ± 11.13) years. Following adjustments for confounding variables, current smoking (OR = 1.26, 95%CI:1.04–1.52) and abdominal obesity (OR = 1.4, 95%CI:1.18–1.66) were significantly linked to an elevated risk of PDM. The multiplicative interaction analyses demonstrated that current smoking exhibited a positive association with PDM (OR = 1.32, 95%CI:1.01–1.71), while a similar association was not observed in the case of abdominal obesity with PDM (OR = 1.15, 95%CI:0.94–1.4). A significant additive interaction was observed between current smoking and abdominal obesity in terms of PDM risk (OR = 3.56, 95% CI: 2.54–4.98). The RERI = 2.09(0.95–3.24), indicating a coexisting risk attributable to additive interaction; the AP = 0.59(0.43–0.75), indicating that 59% of all PDM individuals exposed to both risk factors could be attributed to the synergistic effect of current smoking and abdominal obesity; the SI = 5.51(2.15–14.1), suggesting that the synergistic risk between current smoking and abdominal obesity was 5.51times greater than the sum of effects observed in individuals exposed to a single factor alone. The prevalence of PDM in Rongchang, potentially indicating a higher future incidence of diabetes mellitus. It is noteworthy that smoking and abdominal obesity exhibit a positive synergistic effect on the risk of PDM.